Charts of world religions - House, H. Wayne (Grand Rapids, MI : Zondervan, 2006)
"This collection of charts shows what the major religions of the world have in common and how they differ in terms of beliefs, practices, and understanding of human nature and the supernatural"--Provided by publisher.
Includes bibliographical references (p. 322-336) and index.
Keywords: World Religions -- Charts, diagrams, etc